2014
DOI: 10.1093/mnras/stt2393
|View full text |Cite
|
Sign up to set email alerts
|

On the alignment of PNe and local magnetic field at the Galactic centre: magnetohydrodynamical numerical simulations

Abstract: For the past decade observations of the alignement of PNe symmetries with respect to the galactic disk have led to conflicting results. Recently the first direct observational evidence for a real alignment between PNe and local interstellar magnetic fields in the central part of the Galaxy (b < 5 • ) has been found. Motivated by the recent dicovery we studied the role of the interstellar magnetic field on the dynamical evolution of a planetary nebula by means of an analytical model and from 3D MHD numerical si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…This alignment could have some implications for other studies of GBPNe (see e.g. Rees & Zijlstra 2013;Falceta-Gonçalves & Monteiro 2014;Danehkar & Parker 2016).…”
Section: Kinematic Resultsmentioning
confidence: 54%
“…This alignment could have some implications for other studies of GBPNe (see e.g. Rees & Zijlstra 2013;Falceta-Gonçalves & Monteiro 2014;Danehkar & Parker 2016).…”
Section: Kinematic Resultsmentioning
confidence: 54%
“…For a PN expansion speed of 20 km s −1 , this would mean that the PN reaches the wind termination shock after only 5500 years, which is well within the lifetime of a typical PN. Falceta-Gonçalves & Monteiro (2014) showed simulations of PNe interacting with interstellar magnetic fields and concluded that only very strong fields ( 500 µG) could significantly influence the shape of PNe. However, the study by Falceta-Gonçalves & Monteiro (2014) focused on bipolar PNe.…”
Section: Premisementioning
confidence: 99%
“…CO) are obtained at a temperature range of T = 10 − 10 8 K and gas densities up to 10 12 cm −3 , assuming solar metallicity Z = 1Z⊙. The set of equations is solved using the GODUNOV code 1 (see Kowal & Lazarian 2010;Falceta-Gonçalves et al 2010a,b,c;Kowal et al 2011a,b;Ruiz et al 2013;Santos-Lima et al 2014;Falceta-Gonçalves & Monteiro 2014). The spatial reconstruction is obtained by means of the 5 th order monotonicity-preserving (MP) method (He et al 2011), with approximate HLLC Riemann solver (Mignone & Bodo 2006).…”
Section: Governing Equations and Model Setupmentioning
confidence: 99%